Phytochemical and Mineral Screening of Zanthoxylum Tetraspermum (W & A) - K. Narayanasamy; B. Ragavan (E-Journal of Chemistry)
The present study reveals the phytochemical and mineral screening of Zanthoxylum tetraspermum W & A., a member of the family ‘Rutaceae’, which is used for treating microbial infections, antifungal activities and tooth ache. The preliminary screening of phytochemicals, thin layer chromatographic (TLC) profile of secondary metabolites and minerals from the stem bark of Zanthoxylum tetraspermum have shown the presence of various important secondary metabolites such as alkaloids, flavonoids, glycosides, Phenols, sterols, saponins, tannins in higher levels in hydroethnolic and aqueous extracts and some minerals in the plant extract. The generated data has provided the basis for its therapeutic value and can be used as a therapeutant.